Nutrition strategies for triathlon - Burke, M. L.; Cox, R. G. (Triathlon Medicine, 2019)
Contemporary sports nutrition guidelines recommend that each athlete develop a personalised, periodised and practical approach to eating that allows him or her to train hard, recover and adapt optimally, stay free of illness and injury and compete at their best at peak races. Competitive triathletes undertake a heavy training programme to prepare for three different sports while undertaking races varying in duration from 20 min to 10 h. The everyday diet should be adequate in energy availability, provide CHO in varying amounts and timing around workouts according to the benefits of training with low or high CHO availability and spread high-quality protein over the day to maximise the adaptive response to each session. Race nutrition requires a targeted and well-practised plan that maintains fuel and hydration goals over the duration of the specific event, according to the opportunities provided by the race and other challenges, such as a hot environment. Supplements and sports foods can make a small contribution to a sports nutrition plan, when medical supplements are used under supervision to prevent/treat nutrient deficiencies (e.g. iron or vitamin D) or when sports foods provide a convenient source of nutrients when it is impractical to eat whole foods. Finally, a few evidence-based performance supplements may contribute to optimal race performance when used according to best practice protocols to suit the triathlete`s goals and individual responsiveness.